2018
DOI: 10.25015/penyuluhan.v14i1.16752
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-faktor yang Mempengaruhi Petani dalam Menerapkan Standar Operasional Prosedur (SOP) Sistem Pertanian Organik di Kabupaten Bandung Barat

Abstract: <p><em>Di Kabupaten Bandung Barat banyak petani sayuran yang mulai menjalankan pertanian organic, namun masih terdapat petani yang belum sepenuhnya menjalankan sistem budidaya sayuran organic sesuai dengan SOP. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana penerapan SOP sistem pertanian organic yang dilakukan oleh petani sayuran organic di Kabupaten Bandung Barat serta faktor-faktor yang mempengaruhi petani dalam menerapkan SOP sistem pertanian organic. Penelitian dilakukan di tiga k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
19
0
24

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 8 publications
7
19
0
24
Order By: Relevance
“…The number of farmers participating in counseling and training will distinguish the level of application of organic rice SOPs. The results of this study support the research by [15] concluding that the better the formal education and the more often farmers participate in counseling and training, the easier it is for farmers to cultivate organic vegetables so that there is a tendency for farmers to cultivate organic vegetables in accordance with SOPs. [16] study also revealed that one's knowledge and education greatly influence his ability to adopt an innovation.…”
Section: B Differences In the Application Of Organic Rice Sops Basedsupporting
confidence: 80%
See 1 more Smart Citation
“…The number of farmers participating in counseling and training will distinguish the level of application of organic rice SOPs. The results of this study support the research by [15] concluding that the better the formal education and the more often farmers participate in counseling and training, the easier it is for farmers to cultivate organic vegetables so that there is a tendency for farmers to cultivate organic vegetables in accordance with SOPs. [16] study also revealed that one's knowledge and education greatly influence his ability to adopt an innovation.…”
Section: B Differences In the Application Of Organic Rice Sops Basedsupporting
confidence: 80%
“…The results of data analysis in table 5 show that age does not distinguish the way farmers apply organic rice SOP. As revealed by Sikandar conducting a research in Nalanda Village that the age of farmers did not differ in the level of application of organic rice SOPs [14], and the research in West Bandung District for vegetable commodities [15]. The formal education of farmers will differentiate the level of application of organic rice SOPs in Banjarum Village.…”
Section: B Differences In the Application Of Organic Rice Sops Basedmentioning
confidence: 99%
“…80% of Cassava farmers in calcareous and rain-fed land in Gunungkidul are less than 65 years old which means that they are still in productive age. In the productive age range, a person is in a prime physical condition and is responsive to every change or innovation [10]. A similar situation occurred among the cassava farmers in Southeast Ireland, which was dominated by young farmers of productive age [11].…”
Section: A Characteristics Of Respondentsmentioning
confidence: 83%
“…Usia petani Kelompok Wanita Tani Legowo yang produktif ini dapat memudahkan petani untuk bersikap lebih responsif dan dapat melaksanakan sistem pertanian berkelanjutan dengan baik. Hal ini sesuai dengan pendapatCharina et al (2018) yang menyatakan bahwa petani yang berada pada usia produktif memiliki kondisi fisik yang mendukung untuk melaksanakan kegiatan pertanian dengan baik dan masih memiliki sikap responsif terhadap inovasi.…”
unclassified
“…Pendidikan petani yang tinggi mempermudah dalam penyerapan pengetahuan maupun inovasi yang ada dan pengambilan keputusan yang tepat. Hal ini sesuai dengan pendapatCharina et al (2018) yang menyatakan bahwa pendidikan formal memudahkan seseorang untuk dapat menyerap teknologi dan ilmu pengetahuan serta menentukan sikap dalam pengambilan keputusan yang tepat…”
unclassified